Indoxyl sulfate impairs in vitro erythropoiesis by triggering apoptosis and senescence - Duangchan T. (2023)
Anemia is a major complication in over 50% of chronic kidney disease (CKD) patients. One of the main causes of anemia in CKD is the reduction of erythropoietin (EPO) synthesis from renal tubular cells. Therefore, first-line treatment of CKD is EPO administration; however, EPO unresponsiveness in several patients is frequently found. More undefined causes of anemia in CKD are under interest, especially uremic toxins, which are a group of solutes accumulated in CKD patients. The highly detectable protein-bound uremic toxin, indoxyl sulfate (IS) was investigated for its effects on in vitro erythropoiesis in this study. CD34+ hematopoietic stem cells were isolated from human umbilical cord blood and differentiated toward erythrocyte lineage for 14 days in various concentrations of IS (12.5, 25, 50, and 100 µg/mL). The effects of IS on cell proliferation, differentiation, apoptosis, and senescence were determined. Cell proliferation was investigated by manual cell counting. Cell surface marker expression was analyzed by flow cytometry. Wright’s staining was performed to evaluate cell differentiation capacity. Apoptosis and senescence marker expression was measured using reverse transcription polymerase chain reaction (RT-PCR). TUNEL assay was performed to detect apoptotic DNA fragmentation. Our results demonstrated that IS reduced cell proliferation and impaired erythrocyte differentiation capacity. In addition, this study confirmed the effects of IS on cell apoptosis and senescence during erythropoietic differentiation. Therefore, the promotion of apoptosis and senescence might be one of the possible mechanisms caused by uremic toxin accumulation leading to anemia in CKD patients.